Pro Kontra Sistem Ekonomi Syariah di Indonesia - Rif' Aida Mirza Aurora; Fauzatul Laily Nisa (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
The lack of public understanding of the Islamic accounting system and the minimal number of Islamic economic institutions are the main challenges for the Islamic economy in Indonesia. Many people do not understand how the Islamic accounting system works, leading to uncertainty and misunderstanding about its use. In addition, there are debates between supporters and opponents of this system, which exacerbates the confusion. The small number of Islamic economic institutions also limits people's access to Islamic financial services, so many cannot take advantage of this system. Differences of opinion between practitioners and academics regarding transparency and responsibility in Islamic financial reporting add to the complexity of the issue. To support national economic growth, it is important to analyze the factors affecting the Islamic economy and implement appropriate solutions to overcome these barriers.